Synthesis and Characterization of Vanadia-Doped Iron-Oxide Pillared Attapulgite Clay for the Selective Catalytic Reduction of Nitrogen Oxides - Lu, Yu; Cang, Hui; Han, Fennv; Chen, Zhidong; Xu, Qi (Asian Journal of Chemistry, 2012)
Natural attapulgite was used as the raw material for the preparation of iron pillared clays. The iron-oxide pillared attapulgite was prepared by direct exchange of interlayer sodium cations in attapulgite for iron cations. The performance for the selective catalytic reduction of NOx at low temperature was also investigated. Vanadia (V2O5)-doped iron-oxide pillared attapulgite (V2O5/Fe-P ATP) by impregnation was characterized by X-ray diffraction, surface area and pore size distribution measurement, Fourier-transform infrared spectroscopy and scanning electron microscopy. Modified attapulgite was found to be active and selective for the reduction of Nitrogen oxides with ammonia at low temperatures. Especially at about 220 ºC, the removal ration of NOx was up to 90 %.